Biochemical and Surface Ultra-Structure Investigation of Cholesterol in Local Points and Yamamoto New Scalp Acupuncture (YNSA) for Low Back Pain - Suwaji Handaru Wardoyo; Sholichan Badri (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
Low back pain (LBP) is one of the diseases suffered by people over the world due to musculoskeletal disorders. Blood serum was analyzed for total cholesterol, LDL-C, HDL-C, and triglyceride levels. Cholesterol surface ultrastructure analysis was performed using a SEM microscope. The results showed that total cholesterol and LDL-C levels decreased in the blood serum of LBP patients who had undergone acupuncture therapy by 10 times. Morphology of the surface ultrastructure of cholesterol in the blood serum of LBP patients also showed a reduction in the amount of cholesterol after acupuncture therapy by 10 times. These two results might be useful to improve scientific information for reducing LBP pain, especially through acupuncture therapy.